(untitled) - Cohen, Steven (San Francisco, 1998)
This book introduces public sector professionals to a set of innovation tools: Strategic Planning, Reengineering, Total Quality Management, Benchmarking, Performance Measurement and Management, Team Management, Privatization. It shows how to understand them, use them and integrate them into any organization, and how they will take public managers beyond competence to be creative innovators.
Keywords: Organizational change,Public administration,Tổ chức thay đổi,Hành chính công; Case studies,Case studies,Sự nghiên cứu,Sự nghiên cứu